EUCHARIST: MEANING, THEOLOGICAL INTERPRETATIONS AND THE CONFESSIONAL PERSPECTIVE - dos Santos, Roberto (Revista Gênero e Interdisciplinaridade, 2023)
This academic article on theories of the Holy Supper deals exactly with some aspects of the theological doctrine regarding the meaning of the body and blood of Jesus Christ. It aims to emphasize the confessional theory of the eucharist.